Development of Student Worksheets (LKS) Guided Inquiry-Based Science and Technology Materials in Elementary School - Eli Sasmita; Solfema Solfema; Yalvema Miaz; Zelhendri Zen (Jurnal Penelitian Pendidikan IPA, 2025)
This research was conducted because of the low student learning outcomes. So, the researcher developed a student worksheet. The purpose to be achieved from this research is to produce inquiry-based worksheets that are valid, practical, and effective. This type of research is development research.  The development method used is the Plomp model, which consists of three stages, namely preliminary research, prototyping phase, and assessment stage. Research data were obtained from validity, practicality and effectiveness tests. The results showed that the inquiry-based LKS for grade IV SD developed had met the valid criteria with the characteristics of clear LKS content, in accordance with the curriculum, containing questions that guide students to find learning concepts based on inquiry principles, clear LKS format, sentences and language used are clear, simple, concise and easy to understand, and the presentation is clear. In addition, the LKS developed has also been effective in increasing student learning activities and results with a student learning completeness rate of 91.17%. Based on these results, it can be concluded that the inquiry-based IPAS worksheet developed for grade IV elementary school students is valid, practical, and effective